Resiko Perahu Buatan Masyarakat Tanjungpinang Berdasarkan Hukum Perasuransian - Wishnu Kurniawan; Candra Wira Jaya (Journal of Judicial Review, 2016)
Tanjungpinang wellknown as a Gurindam city is surround by the sea that make most of the people on this coastal area used a traditional boat (pompong) to conduct their daily activity but unfortunately they still don’t have any insurance protections. This research describes clearly and carefully is there any way to register an insurance or making a risk transfer and how to register the insurance for the traditional boat in Tanjung Pinang. This research used normative legal research by using case approach. Data used in form of primary data as supporting data and secondary data. Data were collected by interview and library research. Furthermore, the conclusions drawn from the research, and then elaborated descriptively. This study showed that notwitcstanding the boat which made by Tanjungpinang citizen can be registered to an insurance company but in the end itdepend on insurance company itself whether considered the boats are insurable or not.